Handbook of depression in children and adolescents - Abela, John R.Z; Hankin, Benjamin L. (Guilford Press, 2008)
Offers a review of knowledge on child and adolescent depression, covering from epidemiology and neurobiology to evidence-based treatment and prevention. This book is organized within a developmental psychopathology framework that elucidates the factors that put certain children at risk and what can be done to help.